2017
DOI: 10.1038/s41534-017-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Private quantum computation: an introduction to blind quantum computing and related protocols

Abstract: Quantum technologies hold the promise of not only faster algorithmic processing of data, via quantum computation, but also of more secure communications, in the form of quantum cryptography. In recent years, a number of protocols have emerged which seek to marry these concepts for the purpose of securing computation rather than communication. These protocols address the task of securely delegating quantum computation to an untrusted device while maintaining the privacy, and in some instances the integrity, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 116 publications
(189 reference statements)
0
115
0
Order By: Relevance
“…Quantum information science holds the promise of providing novel capabilities and computational speedups for a host of problems related to computer science [1], secure communication [2][3][4][5][6], the simulation of physical systems [7,8], and distributed computation [9][10][11][12]. One quantum computing paradigm is measurement-based computing [13][14][15] with a highly entangled cluster state (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum information science holds the promise of providing novel capabilities and computational speedups for a host of problems related to computer science [1], secure communication [2][3][4][5][6], the simulation of physical systems [7,8], and distributed computation [9][10][11][12]. One quantum computing paradigm is measurement-based computing [13][14][15] with a highly entangled cluster state (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To reconstruct the 3D image information clearly, the attacker needs to obtain the correct quantum key but also the correct image number, superimposition method, and image reconstruction algorithm. In mathematics, the normalized correlation coefficient (CC) can illustrate the image similarity, and is expressed as [38] CC = N n=1 (a n −ā n ) (e n −ē n ) N n=1 (a n −ā n ) 2 N n=1 (e n −ē n ) 2 (9) where a n andā n (or e n andē n ) are one pixel value and mean of original images (or reconstructed images), respectively. We calculate the CC value by only considering the correct rate of random codes in the quantum key, and the calculated result is shown in Figure 4A.…”
Section: Resultsmentioning
confidence: 99%
“…The protection of information and communication security is critical for the secret document transmission or important from data in order to improve existing methods in machine learning [7,8] ; blind quantum computation is a quantum computation model, which can release the client who does not have enough abundant knowledge and sophisticated technology to perform the universal quantum computation [9,10] ; quantum secure direct communication is to transmit the legitimate parties' secret message directly and securely in a quantum channel without creating a private key to encrypt and decrypt the messages. [11] Previous studies have demonstrated that the hybrid classicalquantum cryptographic technique can provide a very useful strategy to protect the information and communication security.…”
Section: Introductionmentioning
confidence: 99%
“…Blindness may be required to protect user's privacy in future scenarios of delegated quantum computing [53]. In appendix D.2 we thus show how to make our protocol blind.…”
Section: Mesothetic Verification Protocolmentioning
confidence: 99%